Pengelolaan Limbah Plastik Berbasis Ecobrik Untuk Pemberdayaan Masyarakat Dan Keberlanjutan Lingkungan Di Nagari Lawang, Kabupaten Agam Sumatera Barat : Ecobrick-Based Plastic Waste Management for Community Empowerment and Environmental Sustainability in Nagari Lawang, Agam Regency, West Sumatra - Efrizal, Efrizal; Lubis, Amelia Sriwahyuni; Syaiful, Ferry Lismanto; Ulhaq, M. Teguh Dhiya (LPPM Universitas Andalas, 2026)
Indonesia is the world's second-largest contributor to plastic waste, posing a significant environmental challenge due to the extremely slow decomposition of plastic materials, which can take up to 1,000 years. The accumulation of plastic waste has serious environmental consequences, including increased pollution and degradation of ecosystem quality. Therefore, raising public awareness of sustainable waste management has become increasingly important. One practical solution to this problem is the production of ecobricks, which are easy to manufacture using simple tools and readily available materials. This community engagement program aimed to enhance environmental awareness among residents of Nagari Lawang, Agam Regency, West Sumatra, by promoting ecobricks as an innovative approach to plastic waste management and encouraging environmentally responsible behavior to create a cleaner and healthier environment. In addition to reducing plastic waste, ecobricks provide economic opportunities by transforming waste into value-added products that can support community livelihoods. The program was implemented using educational lectures and hands-on demonstrations on converting plastic waste into ecobrick-based gate structures. This participatory approach enabled community members to gain both theoretical knowledge and practical skills in plastic waste recycling. The results showed that participants developed a better understanding of the importance of maintaining environmental cleanliness and public health through proper waste segregation. Furthermore, the community successfully acquired the skills to produce ecobrick products, particularly gate structures, for both household and communal use. Overall, the program contributed to improving environmental awareness, reducing plastic waste accumulation, and empowering the local community through sustainable waste management practices.